THE COMPARISON OF THE EFFECT BETWEEN ALGINATE-BASED RAFT-FORMING LIQUID AND ALGINATE LIQUID ON GASTROESOPHAGEAL REFLUX DISEASE AND GASTRIC ULCER IN RATS - Bangun, Hakim; Arianto, Anayanti; Astya, Ririn; Siregar, Gontar A (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective of the study was to compare the effect between alginate (Alg)-based raft-forming and Alg liquid on healing gastroesophageal reflux disease (GERD) and gastric ulcer in rats. Methods: Each of the 18 fasted rats was given 1 ml acidified pepsin. Then, rats were divided into three groups. Each group consisted of six rats. Group 1 (negative control) was orally given 1 ml distilled water, Group 2 was given 1 ml Alg-based raft-forming liquid, and Group 3 was given 1 ml Alg liquid. Then, the abdomen of rats was incised under anesthesia with ketamine, and then both their pylorus and the forestomach were ligated to form gastric reflux. After 4 hrs, all rats were killed with chloroform and their esophagus and stomach were examined macroscopically and microscopically (histopathology). Results: On macroscopic observation, all of the Group 1 rats (negative control) showed esophageal lesions and gastric lesions. Four rats of Group 2 (given Alg-based raft-forming) showed no esophageal lesion and two more rats showed a slight lesion, but all of the tested rats showed gastric lesions. All of the rats of the Group 3 (given Alg liquid) showed esophageal lesions, but no gastric lesion on four rats and slight lesion on two rats. Microscopic observations showed that all of the Group 1 rats (negative control) showed esophageal erosion and gastric mucosa lesions. Rats of the Group 2 (given Alg-based raft-forming) showed almost no esophageal erosion, but all of them showed erosion of gastric mucosa. Rats of the Group 3 (given Alg liquid) showed esophageal erosion in all tested rats, but almost no gastric mucosa lesion. Conclusion: Alg-base raft-forming liquid is more effective in healing of GERD than Alg liquid. However, Alg-liquid is more effective in healing of gastric ulcer than Alg-based raft-forming liquid.